Effects of a Yoga–DASH Diet program on blood pressure in older adults with hypertension in Bangkok Communities - Warissara Mangkalad; Yupa Jewpattanakul; Rukchanok Koshakri (Journal of Public Health and Development, 2026)
This randomized controlled trial research was aimed at exploring the effectiveness a yoga-DASH diet program applying a revised self- and family management framework on blood pressure for older adults with hypertension in communities in Bangkok. The sample consisted of 106 male and female older adults with hypertension aged 60–75 years and living in Bangkok communities. The sample was obtained by computerized multi-stage sampling. The participants were randomly assigned to either an experimental group or a control group, with 53 individuals in each group. The control group performed normal daily routines, while the experimental group participated in the yoga-DASH diet program for eight consecutive weeks. The program included hypertension education, the DASH diet, ten yoga poses, provision of a handbook, and home visits. The experimental group practiced ten yoga poses and followed the DASH Diet once a week for 8 weeks. The data collection tools included a personal information questionnaire, a DASH diet and yoga practice log, and an automatic blood pressure monitor. All instruments were checked for validity and reliability. The researcher analyzed data before and after the experiment using descriptive analysis, independent t-test and paired t-test statistics. The findings revealed that the older adults with hypertension in the experimental group who participated in the program had significantly lower mean systolic and diastolic blood pressure compared to both baseline and the control group. Paired t-tests showed significant reductions after the intervention in the experimental group (SBP: t = 19.34; DBP: t = 4.78; p < .001), and independent t-tests confirmed significantly lower values compared to the control group (SBP: t = 24.41; DBP: t = 20.75; p < .001).